2006
DOI: 10.1007/s00114-006-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Inducible immune proteins in the dampwood termite Zootermopsis angusticollis

Abstract: Dampwood termites, Zootermopsis angusticollis (Isoptera: Termopsidae), mount an immune response to resist microbial infection. Here we report on results of a novel analysis that allowed us to electrophoretically assess changes in hemolymph proteins in the same individual before and after exposure to a pathogen. We demonstrate that contact with a sublethal concentration of the entomopathogenic fungus Metarhizium anisopliae (Deuteromycotina:Hypomycetes) induces the production of protective proteins in nymphs, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…Wash samples were concentrated with a P10 Microcon filter (Millipore). Hemocytes were isolated from 10 chilled N. corniger workers (1 L per termite) as described (37).…”
Section: Methodsmentioning
confidence: 99%
“…Wash samples were concentrated with a P10 Microcon filter (Millipore). Hemocytes were isolated from 10 chilled N. corniger workers (1 L per termite) as described (37).…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, potential sublethal effects of EPF on honeybees have not been investigated. However, Rosengaus et al (2007) evaluated the contact of a sublethal dose of M. anisopliae on another social insect, the dampwood termite Zootermopsis angusticollis Hagen (Isoptera: Termopsidae) and found that exposure to the fungus induced the production of protective proteins in nymphs, pseudergates (false workers), and soldiers. Exposing honeybees to EPF may provoke a similar immune response, although whether such a response measurably affects colony health or reduces hive activity is another issue and is not known.…”
Section: Biological Controlmentioning
confidence: 99%
“…Pioneering work by, e.g., [18], [19] showed that immunization via sub-lethal dosages of pathogens induces the production of AMPs in the termite hemolymph. A number of genes and peptides related to this kind of humoral immunity have been described in termites.…”
Section: Introductionmentioning
confidence: 99%
“…Among them are a transferrin gene which was up-regulated following exposure to an entomopathogenic fungus [20], termicin, spinigerin [18] and gram-negative binding proteins (GNBPs) which can act as both PRRs and AMPs in several termite species [21]. Production of AMPs appears to differ not only between species [22], but also between termites belonging to different colonies or castes [17], [19], [23]. The components of cellular immunity in termites are less well studied although melanization and encapsulation of foreign bodies have been frequently used as bioassay for immune competence (e.g., [24]).…”
Section: Introductionmentioning
confidence: 99%